The quasi-marketization of Australian public schooling: affordances and contradictions of the new work order. Issue 3 (3rd July 2019) - Hogan, Anna; Thompson, Greg
ABSTRACT: Since the 1990s, public schooling in Australia has been shaped by quasi-marketization that has incentivized competition between schools and installed a business logic to school governance. In this paper we argue that it is timely to consider how teachers and school leaders are understanding and responding to the affordances and challenges of this new "work order". We define this new work order as the languages and practices that are shaping public schooling, particularly in regards to increasing commercialization caused by (and contributing to) the quasi-marketization of schooling. The data gathered for this paper comes from a survey of public school educators who were members of the Australian Education Union (AEU). Our interest is in the perceptions that public school educators had of commercialization in their school system. We show that while many teachers express concerns with the logic behind much education policy, they are far from accepting the new work order. In fact, there was a strong sense of an ethical clash between the managerial nature of much policy and bureaucracy, and strongly held beliefs that public education is justified as a democratic good.